Պարույր Սևակ. հայրենիքը և բանաստեղծը - Գասպարյան, Դավիթ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Паруйр Севак (1924–1971) жил и творил в советские годы, создал свою теорию искусства и занял достойное место в армянской литературе. Его имя звучало и во всесоюзной поэзии того времени, пути которой определяли Андрей Вознесенский, Роберт Рождественский, Евгений Евтушенко, Иосиф Бродский, Владимир Высоцкий, Эдуардас Межелайтис, Иван Драч и другие. Его знали и ценили в этой литературной среде. Он переводил их произведения, они переводили его. Одним из тематических направлений богатой лирики Севака является патриотизм. Армянская литература имеет многовековые и проверенные традиции патриотической лирики. Поэт на национальной основе возобновил эти традиции и создал высокую поэзию, превосходящую требования времени. Paruyr Sevak (1924–1971) lived and created during the Soviet years, developed his own theory of art, and took a worthy place in Armenian literature. His name was also heard in the All-Union poetry of that time, the paths of which were determined by Andrei Voznesensky, Robert Rozhdestvensky, Yevgeny Yevtushenko, Joseph Brodsky, Vladimir Vysotsky, Eduardas Mieželaitis, Ivan Drach, and others. He was recognized and appreciated in this literary environment. He translated their works, and they translated his. One of the thematic directions of Sevak's rich lyrics is patriotism. Armenian literature has centuries–old and proven traditions of patriotic poetry. The poet revived these traditions on a national basis and created high poetry that surpassed the demands of the time.
Keywords: Գրականագիտություն